Peculiarities of surgical treatment of patients with gastroesophageal reflux disease - B. O. Matviychuk; A. R. Stasyshyn; A. A. Hurayevskyy (Клінічна хірургія)
Objective. To analyze the effectiveness of various methods of laparoscopic antireflux operations in patients with gastroesophageal reflux disease.